Relationship of Knowledge, Support of Husband and Body Image with Health Anxiety Levels In Menopausal Women di Working Area Melak Public Health Centers - Susilawangi, Rifkah; Lis Arming Gandini, Andi; Adib Chifdillah, Nino (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Some women consider menopause frightening specter, causing anxiety. Menopausal women in working area Melak Health Center in November 2021-January 2022 are 73 people. Objective: This study aimed to determine the relationship knowledge, husband's support and body image with health anxiety levels in menopause women.  Methods: This type of research is analytic survey with cross sectional design. Results and Discussion: Most of the respondents were aged 56-60 years (61.3%). high school education (41.9%), housewives (59.7%), poor knowledge about menopause (59.7%), husband's support is not supportive (58.1%), body image is not good (64, 5%), experiencing anxiety (62.9%). There is a relationship between knowledge (p value: 0.045), husband's support (p value: 0.003) and body image (p value: 0.036) with the level of health anxiety in postmenopausal women in the working area of the Melak Health Center. Husband's support is the most dominant factor. Anxiety in menopausal women can be related to husband's support, where husbands often pay less attention to menopausal wives and domestic violence can occur.  Conclusion: Knowledge, husband's support and body image are factors related with health anxiety levels in menopause women